PENGEMBANGAN MODUL BERBASIS KONTEKSTUAL PADA MATERI GEOMETRI UNTUK SISWA KELAS X DI SMA PGRI 1 PADANG - Firdaus, Ahmad - (Pendidikan Matematika, 2014)
This research has background with geometry subject abstractive and the material that less guided student to apply geometry subject on daily activity. This research has purpose to know validity and practicality module based on contextually to geometry subject that developed in class X SMA PGRI 1 Padang. The kinds of study are research and development by 4-D model. On define section consists of syllabus analysis, text book analysis, literature analysis and observation with teacher and student. Design section is done planning of module based on contextually, then develop section is done exams validity and practicality. The result of exam module validity shows that this module on characteristic which very valid namely 83%. Result of exam practicality by the teacher shows that this module on practice characteristic namely 80% and the result exam practicality by the student shows that this module on characteristic which very practice namely 84%. The conclusion that module based on contextually on geometry subject is develop by valid and practical.